A Survey of the Effect of Risk Perception and Socioeconomic Status on Coping Strategies in Violent Situations Against Women - Jafari, Zahra; Ghaffarpour, Hosna; Rajezi Esfahani, Sepideh (Psychology of Woman Journal, 2023)
Objective: Violence against women is a severe mental health problem. Much research has been done separately on the perception of risk, socioeconomic status (SES), and coping strategies of women who are victims of domestic violence. This study aims to investigate how women’s risk perception and socioeconomic status affect their choice of coping strategies and to compare women who are victims of violence with women who have not experienced domestic violence. Method: The statistical population is married women in Iran, 312 women were selected as a sample through random sampling. To measure the variables, four questionnaires were used: Ghodratnama’s Socioeconomic Status (SES), Haj-Yahia’s Questionnaire of Violence Against Women, Benthin Risk Perception Scale, and Jalowiec Coping Scale. After the data collection stage, the relationship between the variables was analyzed using SPSS software and Pearson’s correlation and linear regression. Results: In women victims of violence, risk perception was significantly related to fatalistic and palliative strategies, and SES was significantly related to evasive strategy (p<0.05). In women who were not subjected to domestic violence, risk perception had a significant relationship with optimistic, fatalistic, and emotive strategies (p<0.05). The correlation coefficient between risk perception and fatalistic and emotive strategy was very weak and can be ignored. Conclusion: The present study showed that the perception of risk affects the fatalistic and palliative coping strategies of women who are victims of violence, and their low socioeconomic status leads to more use of passive strategies such as evasive. And women who have not experienced domestic violence, the less they see themselves in danger of violence, the more they will use optimistic strategies.